Análise de custos de um centro de beleza e estética em Mossoró: um estudo de caso - Dantas, Josiélio Maia (Universidade Federal Rural do Semi-Árido, 2019)
Within the service sector, the aesthetics and beauty segment has been growing steadily and is a very competitive market. In this context, the present study presented the costs, expenses, as well as information for better decision making as: breakeven point, contribution margin and safety margin, as well as the formation of the orientative selling price through the mark-up index, related to a beauty and aesthetic clinic in the city of Mossoró-RN, with the objective of establishing the absorption costing system and complementing the direct / variable costing system able to support the elaboration of a service pricing strategy, besides evaluating profitability, as well as assisting the control and management of costs by the company's management. For this, it was made a case study using descriptive research with a quantitative approach through documents provided by the company and data from the management software used by it, as well as through informal interviews applied to the partner and their employees. The results of this study indicate that 14 services are the ones that most impact revenues. Among these the services of maintenance of hair extension, traditional brush and maintenance of the prosthesis are the most profitable with unit costs of R$ 81.95, R$ 17.58 and R$ 18.50 respectively. The research contributed to beauty salon managers seeking the best cost strategy, establishing a competitive differential, thus generating a greater understanding about the needs of your company, as well as your customers so that they can achieve excellence in the rendering of services.
Monografia
Keywords: Gestão de Custos; Métodos de Custeio; Análise de Custo/Volume/Lucro; Formação do Preço de Venda; Costs management; Costing Methods; Cost /Volume/Profit Analysis; Sales Price Formation; ENGENHARIAS::ENGENHARIA DE PRODUCAO